Morphometrik Indicators of Wing Girdle Bones in the Postnatal Ontogenesis of Chickens - Najmiddinov, K. (American Journal of Biology and Natural Sciences, 2025)
The dynamics of changes in the linear dimensions and weight of the wing girdle bones of laying hens in postnatal ontogenesis has been studied. It was found that the absolute values of the linear size and mass of the wing belt bones increase intensively from the first day of postnatal ontogenesis to 16 days of age, and this condition continues until the physiological period of chickens, i.e. up to 168 days, and at this age is higher than in chickens of other ages, and the intensity of growth from 280 days to At 570 days of age, it slows down due to the intensification of the egg-laying process. There was an increase in the mass of the growth coefficient of the absolute parameters of the scapula, clavicle and coracoid bones compared with their linear sizes at the physiological stages of postnatal ontogenesis.